American Power in Syria: Ideology, Sovereignty, and Human Rights in the Perspective of International Law - Wajid Fauzi; Ida Rochani; Hindun Hindun (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
The Syrian crisis, which began in 2011 and continues to influence global politics, offers a key case for examining American power. This article explores the ideological and discursive foundations of U.S. involvement, situating it within American Exceptionalism and analyzing it through a Foucauldian framework. The study combines a normative legal approach with critical discourse analysis, drawing on primary sources such as the UN Charter, Security Council resolutions, and U.S. policy documents, along with secondary literature and think-tank reports. Findings show that U.S. intervention is framed through narratives of democracy promotion, humanitarian protection, and global security, which serve to legitimize action. Using Foucault’s concepts of power/knowledge, governmentality, and biopolitics, the study demonstrates that the U.S. not only exercises military force but also shapes global perceptions and constructs regimes of truth. From a transnational legal perspective, these actions reveal tensions between sovereignty and humanitarian imperatives and highlight gaps and asymmetries in international law. The article is novel in integrating ideology, sovereignty, and human rights to show how U.S. actions in Syria reshape the interpretation and application of international law.